2023
DOI: 10.3390/v15020409
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Blood Donor Screening Data: An Under-Recognized Resource for Canadian Public Health Surveillance

Abstract: Hepatitis B surveillance is essential to achieving Canada’s goal of eliminating hepatitis B by 2030. Hepatitis B rates, association of infection with vaccine age-eligibility, and risk factors were analyzed among 1,401,603 first-time Canadian blood donors from 2005 to 2020. Donors were classified as having likely chronic or likely resolved/occult infections based on hepatitis B surface antigen, anti-hepatitis B core antigen, and hepatitis B nucleic acid test results. Likely chronically infected and control dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 29 publications
0
14
0
2
Order By: Relevance
“…Patients and blood donors capture different sub‐populations [24]. Blood donors are deferred for recent risk factors, such as sexual risks, contact with hepatitis infectious sources, such as needlestick exposures, or known history of hepatitis B infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients and blood donors capture different sub‐populations [24]. Blood donors are deferred for recent risk factors, such as sexual risks, contact with hepatitis infectious sources, such as needlestick exposures, or known history of hepatitis B infection.…”
Section: Discussionmentioning
confidence: 99%
“…The median age of referred patients was slightly older than the median age of blood donors. Canadian Blood Services (CBS) has reported that donors tend to skew older, with almost half (45%) of donors over the age of 50 years [34], although first‐time donors are generally younger on average (70% are under the age of 50 years [24]). In contrast, gtE referred patients and blood donors had median and mean ages that were significantly younger than persons infected with other HBV genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…All first-time donors with confirmed syphilis antibody results from 2005 to 2015, and from 2020 to 2021 were invited to participate in a telephone risk factor interview described elsewhere. 20 In brief, four control donors negative for all infectious markers matched by age (±5 years), sex, donation status and region were randomly selected. After notification of their syphilis positive result a letter inviting participation in the interview was sent.…”
Section: Case-controlmentioning
confidence: 99%
“…Therefore, nucleic acid test for circulating HBV DNA was introduced around year 2000 worldwide. 8,9 This new assay is more sensitive than HBsAg in detecting HBV and effectively eliminate window-period carrier donors. Currently, the PTH hepatitis B decreases to less than 1 per 100 000 in Asia-Pacific areas, and this common horizontal HBV transmission route is almost interrupted.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the PTH hepatitis B decreases to less than 1 per 100 000 in Asia-Pacific areas, and this common horizontal HBV transmission route is almost interrupted. 9…”
Section: Introductionmentioning
confidence: 99%